A novel HRM assay for differentiating classical strains and highly pathogenic strains of type 2 porcine reproductive and respiratory syndrome virus. (June 2018) - Sun, Junying; Bingga, Gali; Liu, Zhicheng; Zhang, Chunhong; Shen, Haiyan; Guo, Pengju; Zhang, Jianfeng
Abstract: Differentiation of classical strains and highly pathogenic strains of porcine reproductive and respiratory syndrome virus is crucial for effective vaccination programs and epidemiological studies. We used nested PCR and high resolution melting curve analysis with unlabeled probe to distinguish between the classical and the highly pathogenic strains of this virus. Two sets of primers and a 20 bp unlabeled probe were designed from the NSP3 gene. The unlabeled probe included two mutations specific for the classical and highly pathogenic strains of the virus. An additional primer set from the NSP2 gene of the highly pathogenic vaccine strain JXA1-R was used to detect its exclusive single nucleotide polymorphism. We tested 107 clinical samples, 21 clinical samples were positive for PRRSV (consistent with conventional PCR assay), among them four were positive for the classical strain with the remainder 17 for the highly pathogenic strain. Around 10 °C difference between probe melting temperatures showed the high discriminatory power of this method. Among highly pathogenic positive samples, three samples were determined as positive for JXA1-R vaccine-related strain with a 95% genotype confidence percentage. All these genotyping results using the high resolution melting curve assay were confirmed with DNA sequencing. This unlabeled probe method provides an alternative means to differentiate the classical strains from the highly pathogenic porcine reproductive and respiratory syndrome virus strains rapidly and accurately. Highlights: A simple, sensitive, specific HRM assay with unlabeled probes was established. It is a novel UP-HRM method for differentiating C-PRRSV and HP-PRRSV. The ΔTm value of probe melting temperature is around 10 °C, demonstrating high discriminatory power of this method. HRM assay was verified by sequencing. SNP-HRM was established for differentiating JXA1-R vaccine strain from HP-PRRSV.